ҚАРАҚАЛПАҚСТАНДА ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА ПЕДАГОГИКА ИЛИМИНИҢ РАЎАЖЛАНЫЎЫ - Утебаев, Т.Т. (ILIM hám JÁMIYET, 2019)
The article is devoted to the issues of the development of pedagogical outlook and also the main issues in the system of education and sphere of science in Karakalpakstan for the years of independence. The article points out some problems, opinions of scientists on the theory and history of pedagogics and valuable basic facts about the future of this science. The article can be useful for specialists who take an interest in the theory and history of pedagogics, they can take valuable information.